2012
DOI: 10.3844/ajassp.2012.874.878
|View full text |Cite
|
Sign up to set email alerts
|

Educational Technology Media Method in Teaching and Learning Progress

Abstract: Problem statement:The objective of this research was to evaluate the level of understanding and students' interest in Jawi education, after educational technology media was used in teaching and learning at primary schools. This study emphasizes with more detail on the aspects of usage and effectiveness media-aided teaching system. Exploring the notion of instrument, recognized positive attitude and students associated with the use of educational technology media in teaching and learning process. Approach: A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 6 publications
(7 reference statements)
7
34
0
11
Order By: Relevance
“…Media adalah segala sesuatu yang dapat digunakan untuk mencapai tujuan pengajaran [7]. Media pembelajaran adalah alat bantu apa saja yang dapat dijadikan sebagai penyalur pesan agar tercapai tujuan pembelajaran [8][9] [10]. Sedangkan Android adalah sistem operasi bergerak (mobile operating system) yang mengadopsi operating system Linux, namun telah dimodifikasi [11].…”
Section: Metodeunclassified
“…Media adalah segala sesuatu yang dapat digunakan untuk mencapai tujuan pengajaran [7]. Media pembelajaran adalah alat bantu apa saja yang dapat dijadikan sebagai penyalur pesan agar tercapai tujuan pembelajaran [8][9] [10]. Sedangkan Android adalah sistem operasi bergerak (mobile operating system) yang mengadopsi operating system Linux, namun telah dimodifikasi [11].…”
Section: Metodeunclassified
“…Learning by combining media technology will have a significant influence on learning achievement (Herbert, Ens, Weerasinghe, Billinghurst, & Wigley, 2018;Sakat et al, 2012). Besides, technology can be used as an innovative learning media that is believed can keep up with the developed era (Sakat et al, 2012). The implementation of learning media ICT-based will increase the student learning motivation, as well as student learning outcomes (Harandi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that there are statistical differences in seventh grade student's critical thinking fro history course related to teaching methodology and for the way of the training program which is based on CoRT strategies. Sakat et al (2012) who conducted a research about Education technology media method in teaching and learning progress. The study showed that the Computer usage can stimulate effective learning and improve the performance of Jawi education, enhancing the high level of interactivity among students.…”
Section: Discussionmentioning
confidence: 99%